Spatial variation of water beetle communities in arid and semi-arid Patagonian wetlands and their value as environmental indicators - Epele, Luis Beltran (2012)
To evaluate the spatial variation of aquatic beetle assemblages, 26 Patagonian ponds were sampled during late spring (December).  Study sites differed in hydroperiod, hydrology, abiotic features, precipitation, aridity and aquatic plant richness.  15 physico-chemical features were measured and aquatic plants were collected to determine taxonomic richness.  The sampling of the 26 ponds produced 21 aquatic beetle taxa distributed in six families.  All aquatic beetles (adults and larvae) were assigned to functional feeding groups.  A canonical correspondence analysis (CCA) was run to assess relationships between aquatic beetle assemblages and environmental variables.  23% of the variance in aquatic beetle taxa abundance was accounted for by the first three ordination axes.  Moreover, the first two canonical axes accounted for 38.2% and 28.4% of the variation attributable to the environmental variables (annual precipitation, altitude, pond area, aquatic plant richness, pH and conductivity), being conductivity and altitude the most important.  A parsimony analysis was performed in order to establish which species could define and/or group some of the communities (sampling sites were treated as taxa and species were treated as characters).  The results of the parsimony analysis suggest that some taxa (Haliplus subseriatus, Gymnochthebius sp., Enochrus darwini, Cyphon sp., Luchoelmis sp.  and Rhantus validus) are useful to define some ponds or groups of ponds.  These species could be used as indicators since beetle distributions are not to be considered random.  Our findings point out that aquatic beetle assemblages could be utilised for wetlands conservation planning since in arid and semiarid Patagonia they are important as water reservoirs and also for cattle rearing.